2011
DOI: 10.1007/s12525-011-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of electronic markets research—looking backwards towards the future

Abstract: Over the past 20 years the field of electronic markets has seen a considerable proliferation and differentiation. This position paper takes the opportunity of the 21st volume of "Electronic Markets" to look back at important developments and insights, suggesting a framework that captures the multiple facets and indeed empirical breadth and depths of this concept. It comprises three perspectives which include the market environment, governance choices by economic actors as well as the entrepreneurial dynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 36 publications
(24 reference statements)
2
43
0
4
Order By: Relevance
“…The idea of one-to-one interactions is also in line with recent scholars suggesting a revival of the social component in electronic markets, as consumers and other members of the society are regaining control (Alt & Klein, 2011). As consumers have become active in the service consumption and production (Prahalad & Ramaswamy, 2004), the empowerment of individual employees on the other end of the service continuum need to be considered as key counterparts in a technologyfacilitated interaction of tourism experiences.…”
Section: Personalized Interactions (E2c)mentioning
confidence: 63%
See 2 more Smart Citations
“…The idea of one-to-one interactions is also in line with recent scholars suggesting a revival of the social component in electronic markets, as consumers and other members of the society are regaining control (Alt & Klein, 2011). As consumers have become active in the service consumption and production (Prahalad & Ramaswamy, 2004), the empowerment of individual employees on the other end of the service continuum need to be considered as key counterparts in a technologyfacilitated interaction of tourism experiences.…”
Section: Personalized Interactions (E2c)mentioning
confidence: 63%
“…Smart technologies have become pervasive in electronic markets across a number of areas, including the financial sector, retail and tourism (Alt & Klein, 2011). With the advancement of society and industries coupled with the proliferation of information and communication technologies (ICTs), it has become a critical endeavor to explore the potential of smart technologies for business strategies and competitiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sub-conscious biases, the analysis that follows is expressly motivated by relevance to the real world of electronic interaction, and hence highly values publications that are accessible by practitioners in preference to those written by academics solely for other academics. An article that represents a counterpoint to this paper, with stronger theoretical pedigree and intellectual ambition, is Alt and Klein (2011). That paper is, however, concerned specifically with economic perspectives on electronic markets, which is a small sub-set of the broad field of view of the Bled eConference and the present paper.…”
Section: Introductionmentioning
confidence: 98%
“…To validate this research framework interviews have been conducted among policy makers from the Saudi Ministry of Commerce and Trade. The interview questions were based on the e-businesses literature [8], [5], [11]. However, some e-businesses variables have been explored during the interview with e-businesses experts and these are discussed in section "result discussion" and later presented in the proposed research framework, which is shown in bold in Fig.…”
Section: Methodsmentioning
confidence: 99%